“HA CORRIDO ESTA FAMA Y COMO ANDABA HUYENDO DE LA JUSTICIA, TODO CUANTO MALO SE HACÍA SE LE IMPUTABA". THE COMMUNITY OF LOS HORNOS DE ILLAPEL IN THE CASE OF RAMÓN CORTÉS, 1778-1783 - Girón Zúñiga, Nicolás (Revista de Historia Social y de las Mentalidades, 2016)
This article examines the case of a man  named Ramon Cortés from a micro-historical  perspective. From his judiciary record,  the purpose is to know how the people of  Los Hornos de Illapel were involved in the  prosecution of the case. The aim is to analyze  strategies of social production that took place  in the framework of the judiciary practices in  the eighteenth century in Chile. The work is  part of what has been called "social history  of justice", and contains a reflection on the  community idea and the “publica voz y fama”  formula. The author explains the differences  in the understanding of public fame, from a  social viewpoint and other judicial, linked to  a mechanism of political representation by  judiciary agents.
Keywords: Microhistory; Community; Colonial justice; Local law; Pública voz y fama